2017
DOI: 10.1111/avsc.12289
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of long‐term ungulate impact: increase of plant species richness in a temperate forest

Abstract: Contrary to our expectations, our long-term data showed that artificially high ungulate densities substantially increased plant species richness. Apparently, the establishment of ruderal herbs was supported by frequent disturbances and ungulate-mediated dispersal. At the same time, species richness of non-ruderal plants did not change, probably because ungulates hindered the regeneration of woody species and maintained an open forest canopy. In conclusion, high ungulate density led to the spread of ruderal spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…The declining species richness of European lowland forests is considered to be a result of the cessation of traditional forest management (Hédl et al., ; Kopecký et al., ) and environmental eutrophication and acidification (Baeten et al., ; Becker, Spanka, Schröder, & Leuschner, ; Jantsch, Fischer, Fischer, & Winter, ). However, changes in species richness are variable and some recent studies actually found increasing species richness in European forests (Förster, Becker, Gerlach, Meesenburg, & Leuschner, ; Reczyńska & Świerkosz, ; Vild et al., ; Strubelt, Diekmann, & Zacharias, ). The species richness of studied sub‐montane forests declined significantly, but the magnitude of these changes was relatively small compared to lowland forests (Bernhardt‐Römermann et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The declining species richness of European lowland forests is considered to be a result of the cessation of traditional forest management (Hédl et al., ; Kopecký et al., ) and environmental eutrophication and acidification (Baeten et al., ; Becker, Spanka, Schröder, & Leuschner, ; Jantsch, Fischer, Fischer, & Winter, ). However, changes in species richness are variable and some recent studies actually found increasing species richness in European forests (Förster, Becker, Gerlach, Meesenburg, & Leuschner, ; Reczyńska & Świerkosz, ; Vild et al., ; Strubelt, Diekmann, & Zacharias, ). The species richness of studied sub‐montane forests declined significantly, but the magnitude of these changes was relatively small compared to lowland forests (Bernhardt‐Römermann et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to detect biotic homogenization not only depends on the temporal and spatial scale, but also on the overall variability of vegetation types under consideration (McCune & Vellend, ). Nevertheless, the vegetation homogenization of Central European forests has been reported in studies focused on only one or a few forest vegetation types at small spatial scales (Hülber et al., ; Šamonil & Vrška, ; Durak & Holeksa, ; Heinrichs & Schmidt, ; Vild et al., ). Few studies have explored changes in vegetation variability at a spatial scale comparable with that considered in our study: forest patches in the south of England homogenized since the 1930s (Keith et al., ) and a broad‐leaved forest in northern Germany homogenized during the 1990s (Naaf & Wulf, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important limitation of such studies is their constrained ability to test the ecological mechanisms underlying temporal community change. Indeed, most legacy studies pertain to a single site or region, meaning a set of plots within an area sharing a similar climate and history, in which case community change might be caused by many local changes, such as ongoing land use (Hermy & Verheyen, 2007;Kampichler, van Turnhout, Devictor, & van der Jeugd, 2012;Newbold et al, 2015), historical management legacies (Becker, Spanka, Schröder, & Leuschner, 2016;Perring et al, 2017;Vanhellemont, Baeten, & Verheyen, 2014), nitrogen deposition (Becker-Scarpitta, Bardat, Lalanne, & Vellend, 2017), or grazing (Frerker, Sabo, & Waller, 2014;Vild et al, 2016).…”
mentioning
confidence: 99%
“…An important limitation of such studies is their constrained ability to test the 55 ecological mechanisms underlying temporal community change. Indeed, most legacy 56 studies pertain to a single site, meaning a set of plots within an area sharing a similar 57 climate and history, in which case community change might be caused by many local 58 changes, such as ongoing land use (Hermy & Verheyen, 2007;Kampichler et al, 2012;59 Newbold et al, 2015), historical management legacies (Vanhellemont et al, 2014;60 Becker et al, 2016;Perring et al, 2017), nitrogen deposition (Becker-Scarpitta et al, 61 2017) or grazing (Frerker et al, 2014;Vild et al, 2016). 62…”
mentioning
confidence: 99%